René Maran : genèses de la première édition (1921) de Batouala, véritable roman nègre, et de sa préface - Charles W. Scheel (Continents manuscrits)
The point in this contribution is to update what is known about the genesis of René Maran’s novel Batouala and the genesis of its preface, penned by the author himself. On the basis of documents available in various archives, between late 1909 (when young Maran left Bordeaux for the Oubangui-Chari) and July 1921 (when the novel was published by Albin Michel in Paris). The most significant passages of the remarquable studies published on this issue by Léon Bocquet in 1924 and Manoel Gahisto in 1965 will be brought back to memory and followed by a section quoting from hitherto unpublished correspondances with relevance to : 1) initiatives taken by either Maran or Gahisto to find a publisher for the novel in Paris ; 2) the writing of the famous preface ; and 3) the entering of the novel in the competition for literary awards – upon instructions by the author, prior to his precipitated return to Africa in February 1921.